MicroRNA 375 modulates hyperglycemia-induced enteric glial cell apoptosis and Diabetes-induced gastrointestinal dysfunction by targeting Pdk1 and repressing PI3K/Akt pathway - Chen, Yan; Liu, Gongxiang; He, Fuqian; Zhang, Li; Yang, Kun; Yu, Huan; Zhou, Jinqiu; Gan, Huatian (Scientific reports, 2018)
Diabetic neuropathy can damage systemic nervous system, including alteration of enteric nervous system and subsequent gastrointestinal dysfunction. The effect of diabetes on enteric glia cell (EGC) is not clear. We investigated the effect of diabetes and hyperglycemia on EGC, and the role of microRNA375 in modulating EGC survival in vivo and in vitro . Streptozotocin-induced diabetic mice were intraperitoneally injected with microRNA375 inhibitor or its negative control. EGC was transfected with microRNA375 inhibitor or its mimic. Diabetes mice with gastrointestinal dysfunction showed increased apoptosis of EGC (no difference in cell numbers) and gene expression of micorRNA375 in the myenteric plexus. Hyperglycemia triggered apoptosis of EGC in vitro with decreased expression of Pdk1 and p-Akt, but increased expression of micorRNA375. MicorRNA375 mimic induced apoptosis of EGC in vitro with repressed Pdk1and p-Akt. MicorRNA375 inhibitor could both prevent hyperglycemia-induced apoptosis of EGC in vitro and diabetes-induced gastrointestinal dysfunction in vivo . Our results suggest that diabetes-induced gastrointestinal dysfunction is related to increased apoptosis of EGC in the myenteric plexus. Hyperglycemia can increase the expression of microRNA375 and damage EGC survival through PI3K/Akt pathway. MicroRNA375 specific inhibition can prevent hyperglycemia induced EGC damage and diabetes-induced gastrointestinal dysfunction.